2016
DOI: 10.3389/fimmu.2016.00098
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MIF Gene Promoter Variations on Risk of Rheumatic Heart Disease and Its Age of Onset in Saudi Arabian Patients

Abstract: Although macrophage migration inhibitory factor (MIF) has consistently been shown to be an important immune modulator, data on the association between MIF promoter variations and the risk of developing rheumatic heart disease (RHD) remain inconclusive. RHD is an important complication of streptococcal infections in the Middle East, not least in Saudi Arabia, and identifying risk markers is an important priority. Therefore, we investigated the association between two functional MIF promoter variations and RHD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…1): RA with SLE and psoriasis (Lin et al 1998; Alarcon-Segovia et al 2005; Naldi and Mercuri 2010), MS and asthma with psoriasis (Fang et al 2015; Egeberg et al 2016), and RF with scarlet fever and throat/ear infections (Soderholm et al 2018). We also found an association between IBD and RF, consistent with preliminary evidence for shared genetic risk (Abdallah et al 2016) and data linking IBD with other immune-mediated diseases (Halling et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…1): RA with SLE and psoriasis (Lin et al 1998; Alarcon-Segovia et al 2005; Naldi and Mercuri 2010), MS and asthma with psoriasis (Fang et al 2015; Egeberg et al 2016), and RF with scarlet fever and throat/ear infections (Soderholm et al 2018). We also found an association between IBD and RF, consistent with preliminary evidence for shared genetic risk (Abdallah et al 2016) and data linking IBD with other immune-mediated diseases (Halling et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…28,29 The choice of single-nucleotide polymorphisms tested in the present study was principally based on earlier reports. [9][10][11][12]14,15,18,28 Baugh et al identified a functionally significant polymorphism in the human MIF gene, consisting of CATT repeats at position -794 of the MIF promoter. 15 The 5-CATT repeat display lowers promoter activity when compared to the 6-, 7-, or 8 repeat alleles.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Polymorphisms in the promoter region of MIF gene, that is, CATT tetranucleotide repeat at -794 (rs5844572) or guanine (G) to cytosine (C) transition at -173 (-173*G/C, rs755622) have been reported to be associated with increased susceptibility to, or severity of, numerous chronic inflammatory, and autoimmune disorders in different populations. [4][5][6][7][8][9][10][11][12][13][14][15][16] Given these data, the pharmacological or immunological modulation of MIF activity might offer new therapeutic options for patients suffering from these diseases. 6 We planned this study to see whether MIF gene polymorphisms affect the susceptibility to and severity of chronic plaque psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…A few more genes have been linked to RHD in different studies, but there are currently no meta-analyses to confirm or reject these findings. Macrophage migration inhibitory factor ( MIF ) promoter polymorphisms -173C and -794 (5-8 CATT repeats) have been associated with RHD age of onset in a Saudi Arabian population ( 53 ). The C allele at−173 was associated with higher MIF expression in T cell lines ( 54 ).…”
Section: The Genetics Of Rhdmentioning
confidence: 99%